2013
DOI: 10.1111/jgh.12159
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molecular adsorbent recirculating system on renal recovery in type‐1 hepatorenal syndrome patients with chronic liver failure

Abstract: MARS therapy improved renal function in only very few patients with HRS1. Further controlled studies including large number of patients are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Endotoxins can cause constriction of both renal and peripheral blood vessels, a decrease in renal blood flow, and a decline in GFR. Ultimately, this results in oliguria and azotemia [78].…”
Section: Pathogenesismentioning
confidence: 99%
“…Endotoxins can cause constriction of both renal and peripheral blood vessels, a decrease in renal blood flow, and a decline in GFR. Ultimately, this results in oliguria and azotemia [78].…”
Section: Pathogenesismentioning
confidence: 99%
“…Wong et al performed a study involving six type 1 HRS patients with refractory ascites that had failed vasoconstrictor treatment [ 62 ] and found that MARS was not associated with significant improvements in the GFR, neurohormonal levels, or systemic haemodynamics. In a study of 32 patients, Lavayssière et al found that only 28% of type 1 HRS patients showed complete renal recovery after 28 days [ 63 ]. More recently, a large randomised controlled trial (RELIEF) involving 19 European centres comparing MARS with standard therapy in patients with acute-on-chronic liver failure [ 64 ] reported that while MARS provided temporary organ benefit (liver, kidney, and brain), it did not improve overall survival.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…A more recent study demonstrated that MARS was ineffective in improving systemic haemodynamics in six patients with type 1 HRS who failed vasoconstrictor treatment; only transient reduction in serum creatinine occurred [84]. Another study on 32 HRS-1 patients reported a rate of complete renal response of 28% (9/32) [85]. Prometheus employs fractional plasma separation, and adsorption with haemodialysis could be utilized to treat liver failure patients who have a need for RRT.…”
Section: Therapy Of Hrs: Dialysismentioning
confidence: 99%